Negotiating Two Worlds: Learning through the Stories of Haudenosaunee Youth and Adults - Bomberry, Michelle (Canadian Journal of Education/Revue canadienne de l'éducation, 2013)
Elaborating on this form of knowledge I will share the interconnectedness epistemology as a philosophical understanding for the Haudenosaunee community. Premising the The Kashwenta (Two Row Wampum Treaty) as a foundation, this paper will examine Six Nations’ cultural connectedness through the Tree of Peace analogy and offer an understanding of the disconnected realities occurring at Six Nations of the Grand River Territory. Sixty-eight Six Nation youth and adults participated in discussions about educational experiences and related issues facing Six Nations youth. The themes were placed within the Haudenosaunee Creation Story’s Tree of Peace’s growth stages: Planting the Seeds/Germination, Supports, Branching Out, Threats, Fulfillment, and Journeying On. The participants’ stories illustrate areas Haudenosaunee epistemology can contribute to holistic community strategies and approaches.